2009
DOI: 10.1128/iai.01113-08
|View full text |Cite
|
Sign up to set email alerts
|

Identification of an Essential Francisella tularensis subsp. tularensis Virulence Factor

Abstract: Francisella tularensis, the highly virulent etiologic agent of tularemia, is a low-dose intracellular pathogen that is able to escape from the phagosome and replicate in the cytosol. Although there has been progress in identifying loci involved in the pathogenicity of this organism, analysis of the genome sequence has revealed few obvious virulence factors. We previously reported isolation of an F. tularensis subsp. tularensis strain Schu S4 transposon insertion mutant with a mutation in a predicted hypothetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
136
1
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(143 citation statements)
references
References 63 publications
5
136
1
1
Order By: Relevance
“…Previously, it was demonstrated that the deletion of gene coding for the FTT_1103 or FTS_1067 resulted in the attenuation in mouse model of infection and in the defect in proliferation in vitro [4,5]. Therefore, the effect of complementation was also studied by in vitro proliferation of the complemented strain in murine bone marrow-derived macrophages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, it was demonstrated that the deletion of gene coding for the FTT_1103 or FTS_1067 resulted in the attenuation in mouse model of infection and in the defect in proliferation in vitro [4,5]. Therefore, the effect of complementation was also studied by in vitro proliferation of the complemented strain in murine bone marrow-derived macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…holarctica strain LVS, also referred to as FipB) with proved oxidoreductase and isomerase activities [1][2][3]. It was shown that the deletion of the gene encoding DsbA led to the high attenuation in vivo associated with the ability to induce host-protective immunity [4,5]. Recently, it was presumed that the DsbA is not a virulence factor by itself but that its substrates, whose correct folding and topology are dependent on the DsbA oxidoreductase and/or isomerase activities, are real virulence factors [2].…”
Section: Introductionmentioning
confidence: 99%
“…However, the function of the protein FTT1103 remains unknown. The FTT1103 mutant strain was found to be defective in intracellular growth and it was observed that in BALB/c monocyte/macrophage cell line J774A.1 has a decreased ability to escape the phagosome [26]. Despite its requirement for virulence, this protein is not an essential protective antigen.…”
Section: Novel Essential Virulence Factor Of F Tularensismentioning
confidence: 99%
“…According to the LipoP prediction program (http://www.cbs.dtu.dk/ services/LipoP/, January, 2010), FTT1103 seems to be a membrane lipoprotein [27]. It is highly probable that protein FTT1103 belongs to a group of periplasmatic proteins [26], because its N-terminal signal peptide is eliminated via signal peptidase II [27]. The locus FTT1103 is predicted to encode a hypothetical lipoprotein which shares some similarity to DsbA proteins that catalyze disulfide bond formation.…”
Section: Novel Essential Virulence Factor Of F Tularensismentioning
confidence: 99%
See 1 more Smart Citation